O fim escrito no início: contribuições de Fausto de Goethe à Psicanalise - Zacharewicz, Fernanda (2018)
The aim of this thesis was to research the contributions of Faust by Goethe to the Psychoanalysis. For that we left from the hypotesis of which the repetition is a psychoanalytic concept marking the end of analysis. To comprove that, after a brief incursion by Goethe’s biography and the location of the book in the german’s literature history, it was necessary to get deep into our comprehension on the entry of the subject in the language, on the lack from there and differentiate of the lack relative to the castration. Next we lean over on the wish perspective from Aristotle in De Anima and Nicomachean Ethics from there to understand the construction of this concept in the Psychoanalysis. Beginnig with the text Project for a scientific psychology by Freud we follow up to arriving in Lacan and his comprehension of das Ding. That said, it was possible to base the structure of the subject of langage while lacking and to understand the paradox exposed in the pact between Faust and Mephistopheles. The phantasy was the next point to be study. Therefore, we came back to the firsts Freud’s clinical reports and we follow the construction of this notion. We returned to the concept of unheimlich to understand the anguish that wraps the bascule inherent to the fantasmatic veil. We follow with Lacan in his seminar about anguish untill his seminar about the logic of phantasy. Than, we analysed two moments of Goethe’s text – the relationship of Faust with Gretchen and, in a second moment, his relationship with Helen. We realized how in the litterary text the bias through wich the phantasy can be seen leaves space to the real appears. From the advent of the real in the relationship with Helena comes up to Faust the possibility of a new know-how different from what had been done so far. This contingency opens the possibility to think the repetition as the advento f the new, as Lacan works since 1964. With that in our horizon, we follow the constrution of this concept from Freud in two moments: in 1914 and in 1920. Next, we turno to the lacanian text and divide then in two parts: before and after 1964. We realized then that the written texts or seminars given up to 1964 were directed to the freudian notion of compulsion to repetition. Even so, it is possible to observe in this period some seeds of his future position. The considerations explained here led us to consider the end of faust as the relaization of repetition as a contingency, a bon heur to wich teh subject under analysis can choose by the of his course